Phototherapy in sclerotic skin diseases - Żmuda, Bartłomiej; Ślusarczyk, Daniel; Pisera, Piotr; Kiełkowicz, Aleksandra; Popińska, Zuzanna; Pactwa, Filip; Jakubowska, Wiktoria; Żuberek, Michał (Journal of Education, Health and Sport, 2023)
Introduction: UVA therapy is used in treatment of wide range of skin diseases, which proceed with hardening of the skin or inflammation. First use of ultraviolet radiation can be tracked down to 1896. Wavelength vary among diseases against which it is used. In literature as results of therapy are mentioned improvement of skin elasticity, reduction of inflammation, and protection from relapse. In terms of sclerotic skin diseases most promising effect is seen in reducing skin hardness in the mechanism of stimulating collagen breakdown. The therapy itself has a good safety profile, but is time-consuming due to the high frequency of irradiation. Effectiveness of treatment are determined by factors such as advancement of skin lesions, pigmentation and the intensity of the therapy itself. Aim of study: The aim of the study is to summarize the available knowledge about the UVA therapy in skin diseases. The way of work, effectiveness of treatment, side effects and potential new methods of use were summarized and described. Materials and methods: The literature available in PubMed database was reviewed using following keywords: “UVA therapy”, “UVA”, “Scleroderma”, “Buschke’s Scleredema”, “Systemic sclerosis”, “Morphea” Conclusion: UVA1 therapy is one of the most effective therapeutic options in subtypes of morphea which affect only superficial tissues. Phototherapy accelerate healing of ulcerations on fingertips in patients with Systemic sclerosis. Patient suffering from Buschke Sclerederma had good response to therapy. Observed side effects consist of hyperpigmentation, erythema, xerosis and pruritus in range from mild to severe. Carcinogenic effect has not yet been proven.